The dual diversity crisis in alzheimer's disease research: why neuroimaging biomarkers and clinical trials keep failing - Thorsten Rudroff (GeroScience, 2026)
Alzheimer's disease clinical trials have failed at a rate exceeding 99% over two decades, and neuroimaging biomarkers developed in discovery cohorts have repeatedly disappointed in validation and clinical application. Standard explanations address symptoms rather than structural causes. I argue that Alzheimer's disease research is caught in a Dual Diversity Crisis: the simultaneous neglect of population diversity and individual neurobiological heterogeneity as compounding validity threats. The first dimension concerns the systematic over-reliance on Western, young, healthy, and university-affiliated (WYHU) research samples, from which biomarker normative standards are derived and then applied universally to a demographically distinct clinical population. The second concerns the erasure, through group-level analysis, of the substantial neurobiological heterogeneity that exists within any sample regardless of its demographic composition. The critical structural insight is that these two problems do not add; they multiply. A WYHU-derived group average is doubly unrepresentative: it misrepresents the target population demographically and conceals the individual variance that exists even within that already-unrepresentative sample. FDG-PET evidence demonstrates that biological sex accounts for approximately 30 times more metabolic variance than diagnostic category in patients with equivalent symptom profiles, directly challenging the construct validity of threshold-based trial inclusion. Correcting the Dual Diversity Crisis requires treating demographic diversity and individual neurobiological characterization as primary design parameters, not post-hoc corrections. Until this reconceptualization occurs, translational failure in Alzheimer's disease research remains the structurally expected outcome.

Frontal-striatal glucose metabolism and fatigue in patients with multiple sclerosis, long COVID, and COVID-19 recovered controls - Thorsten Rudroff (Experimental Brain Research, 2024)

Fatigue and perceived fatigability, not objective fatigability, are prevalent in people with post-COVID-19 - Alexandra C. Fietsam; Andrew D. Bryant; Thorsten Rudroff (Experimental Brain Research, 2023)

Cerebellar Contributions to Motor Impairments in People with Multiple Sclerosis - Alexandra C. Fietsam; Warren G. Darling; Jacob J. Sosnoff; Craig D. Workman; John Kamholz; Thorsten Rudroff (The Cerebellum, 2021)

Increased leg muscle fatigability during 2 mA and 4 mA transcranial direct current stimulation over the left motor cortex - Craig D. Workman; John Kamholz; Thorsten Rudroff (Experimental Brain Research, 2020)

Changes in muscle fascicles of tibialis anterior during anisometric contractions are not associated with motor-output variability of the ankle dorsiflexors in young and old adults - Mark Jesunathadas; Thorsten Rudroff; Roger M. Enoka (European Journal of Applied Physiology, 2010)

Muscle activity differs with load compliance during fatiguing contractions with the knee extensor muscles - Thorsten Rudroff; Jamie N. Justice; Stephen Matthews; Rena Zuo; Roger M. Enoka (Experimental Brain Research, 2010)

Discharge of biceps brachii motor units is modulated by load compliance and forearm posture - Thorsten Rudroff; Kimberlee Jordan; Joel A. Enoka; Stephen D. Matthews; Stéphane Baudry; Roger M. Enoka (Experimental Brain Research, 2010)

Discharge rate during low-force isometric contractions influences motor unit coherence below 15 Hz but not motor unit synchronization - Evangelos A. Christou; Thorsten Rudroff; Joel A. Enoka; François Meyer; Roger M. Enoka (Experimental Brain Research, 2007)